The relative role of plasticity and demographic history in Capsella bursa-pastoris: a common garden experiment in Asia and Europe. Issue 3 (2nd April 2022) - Cornille, Amandine; Tiret, Mathieu; Salcedo, Adriana; Huang, Huirun R; Orsucci, Marion; Milesi, Pascal; Kryvokhyzha, Dmytro; Holm, Karl; Ge, Xue-Jun; Stinchcombe, John R; Glémin, Sylvain; Wright, Stephen I; et al.
Abstract: The colonization success of a species depends on the interplay between its phenotypic plasticity, adaptive potential and demographic history. Assessing their relative contributions during the different phases of a species range expansion is challenging, and requires large-scale experiments. Here, we investigated the relative contributions of plasticity, performance and demographic history to the worldwide expansion of the shepherd's purse, Capsella bursa-pastoris . We installed two large common gardens of the shepherd's purse, a young, self-fertilizing, allopolyploid weed with a worldwide distribution. One common garden was located in Europe, the other in Asia. We used accessions from three distinct genetic clusters (Middle East, Europe and Asia) that reflect the demographic history of the species. Several life-history traits were measured. To explain the phenotypic variation between and within genetic clusters, we analysed the effects of (i) the genetic clusters, (ii) the phenotypic plasticity and its association to fitness and (iii) the distance in terms of bioclimatic variables between the sampling site of an accession and the common garden, i.e. the environmental distance. Our experiment showed that (i) the performance of C. bursa-pastoris is closely related to its high phenotypic plasticity; (ii) within a common garden, genetic cluster was a main determinant of phenotypic differences; and (iii) at the scale of the experiment, the effect of environmental distance to the common garden could not be distinguished from that of genetic clusters. Phenotypic plasticity and demographic history both play important role at different stages of range expansion. The success of the worldwide expansion of C. bursa-pastoris was undoubtedly influenced by its strong phenotypic plasticity. Abstract : The respective role of demography, plasticity and adaptation in the colonization success of plant species remains an intense topic of investigation in evolutionary ecology and genomics. A screening of phenotypic traits of hundreds of genotypes in large-scale common garden experiments in Eastern Asia and Europe shows that both demography and a high phenotypic plasticity underlie the success of the tetraploid and self-fertilizing species, Capsella bursa-pastoris, the shepherd's purse, at different stages of expansion. This study provides insight into the causes of the ecological success of a plant species during range expansion.